(untitled) (Journal of history, 2022)
The article deals with fragments of ceramics originating from the archaeological complex of the Bronze Age located on the terraces above the floodplain at the exit of the Rakhat River from the gorge of the same name, between the cities of Talgar and Esik along the road to the gorge. Orman and 1.5 km southeast of the ancient settlement of Rakhat. The complex consists of a settlement and memorial and burial fences of the Bronze Age. This monument was studied by the State Historical and Cultural Museum-Reserve “Esik”. The settlement and mounds have layers of the Saka community, early and late Middle Ages. The main materials i.e. archaeological sources for the interpretation of the cultural layers of the site are fragments of ceramics of the Bronze Age and the Early Iron Age. This article will consider fragments of ceramics and tools of the Bronze Age. The task of the study was the scientific attribution of ceramic fragments based on the traces of work, the identification of separate groups among them with features characteristic of each series, and the restoration to some extent of those production processes that took place in the economy of the tribes of the Bronze Age. To achieve this goal, a comparison and comparative typological analysis of artifacts from the collection of ceramics of the Bronze Age of the Central State Museum of the Republic of Kazakhstan was carried out. Ceramics is the most widely used material in any archaeological site. Definable fragments of ceramics are reliably associated with their own characteristics, for example, pottery school, visual culture, sign system, etc. An analysis of the studied artifacts shows that in the Bronze Age, traditional stone tools were mainly used, which were used in metallurgy and ceramic production in the extraction and processing of minerals, successively associated with the previous era. These are tools used in mining, copper smelting, agriculture, hunting and domestic crafts. Key words: Rahat settlement, ceramics, collection, bronze Age, typology, archaeological expedition, settlements, analysis, monument, foothills of Ile Alatau